齿轮新材料的选择—水平连铸ADI - 王海生; 黄志强; 时胜利 (Jixie chuandong)
This article compares and analyses the gear material of continious casting ADI with steel from the requirement of gear performance. It introduces the possibility of improving performance while cutting cost via application of continios casting ADI. This paper also lists successful applications and popularations of this material in advanced foreign countries, and has a prospect of the application of this material in gears.